(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
This study focuses on the development of the GUnify Information Management System as a platform to validate the effectiveness of the Deflate compression algorithm in optimizing storage requirements for associations with limited resources. GUnify addresses the challenges of managing memberships, events, web portals, and financial reports, providing a cost-effective solution for organizations unable to procure high-end computing resources. Integrating the Deflate algorithm significantly reduces data storage and transmission costs while maintaining performance and functionality. Developed iteratively using Agile Scrum methodology, GUnify adapts to evolving organizational needs and fosters stakeholder collaboration. Its architecture includes Membership Management, Event Management, Web Portal, and Finance Management modules, enabling process automation and enhanced data integrity. The Deflate algorithm ensures efficient storage and retrieval of key data such as member profiles, event schedules, financial reports, and transaction histories. Workflow diagrams illustrate how automation reduces manual tasks and supports decision-making. Additionally, the system's software quality was rigorously evaluated using the ISO 25010 standard, ensuring compliance with criteria such as functional suitability, performance efficiency, usability, reliability, security, and maintainability. This study demonstrates that the Deflate algorithm is a viable solution for optimizing storage and operational efficiency in resource-constrained environments, making GUnify a practical and scalable tool for association management.